The effect of decellularized tissue engineered constructs on periodontal regeneration. (17th April 2018) - Farag, Amro; Hashimi, Saeed M.; Vaquette, Cedryck; Bartold, Peter M.; Hutmacher, Dietmar W.; Ivanovski, Saso
Abstract: Aim: To evaluate the effect of decellularized tissue engineered constructs on cell differentiation in vitro and periodontal regeneration in vivo. Materials and Methods: Periodontal ligament cell (PDLC) sheets were loaded on polycaprolactone (PCL) scaffolds and then decellularized. Constructs were assessed for their effect on allogenic PDLC and mesenchymal stem cell (MSC) differentiation in vitro, as evaluated by gene expression of bone and periodontal ligament tissue markers post‐seeding. Expression of MSC marker STRO‐1 was assessed by immunostaining. Decellularized constructs were evaluated in a rat periodontal defect model to assess their biocompatibility and tissue integration. Microcomputed topography (μCT) and histological assessment were performed to assess the regenerative potential of the constructs at 2 and 4 weeks postoperatively. Results: There was upregulation of bone marker gene expression by PDLCs especially on the 14th day. MSCs lacked bone markers expression, but showed increased collagen I marker expression on day 14. STRO‐1 expression by the MSCs decreased over the three timepoints when seeded on decellularized sheets. Histological assessment demonstrated the biocompatibility of the decellularized constructs in vivo. More new attachment formation was observed on the decellularized constructs compared to scaffold only controls. Conclusion: Decellularized tissue engineered constructs are capable of inducing cell differentiation in vitro and have the potential to facilitate periodontal regeneration in vivo.